Merdeka Belajar Kampus Merdeka: Application in Education Faculty - Tuti Marjan Fuadi; Irdalisa Irdalisa (STAI Hubbulwathan Duri, 2021)
The independence policy is a hot topic in the world of education. The premise that learning exists is carried out in the preparation of university graduates, both public and private, to meet the modern-day and rapid change challenges. Independent learning is a notion that aspires to excel from graduates as future leaders with an increasing number of personalities. Independent programs provide students with independence and flexibility to develop their potential through their hobbies and talents. This study will first examine the format of the eight Merdeka Belajar Kampus Merdeka programs (MBKM) featured in the Merdeka Independent Campus Free Book released by the Ministry of Education and Culture's Directorate General Higher Education (Published in 2020). Second, a variant of MBKM that was adopted in the Odd and Even semesters of the 2020/2021 Academic Year at a university in Aceh's Faculty of Teacher Training and Education. The findings indicated that there were eight Merdeka Belajar Kampus Merdeka programs, including the following: 1) student exchange, 2) internship/work experience, 3) teaching in educational institutions, 4) village projects, 5) research, 6) entrepreneurial activities, 7) independent studies, and 8) humanitarian projects. The Faculty of Teacher Training and Education has run a student exchange program with another university, a teaching assistant program in educational institutions, and a program to build villages/thematic lectures for students and lecturers who passed the selection process for a grant program called